Capitalism is groovy, but at what cost? - Krishna Vedala; Phillip T Sobash; Shiyu Wang; Gilbert-Roy Kamoga (Journal of Community Hospital Internal Medicine Perspectives, 2020)
Due to the COVID-19 pandemic, the FDA was forced to bypass normal protocol and issue Emergency Use Authorization for diagnostic testing. As a result, we have seen an explosion in the number of available molecular diagnostic tests developed by various private enterprises. Our case reports of an 85-year-old female who was suffering from a multitude of co-morbidities and underwent three different molecular diagnostic tests in a short timeframe. With little data on the precision and reliability of the multiple available tests, it has become extremely difficult to diagnose and guide management. Instead of focusing on commercial ventures, FDA in conjunction with the CDC should prioritize our resources to tackle COVID-19 as a public health crisis.